Fontes de satisfação no esporte e ativos de desenvolvimento : estudo com atletas do estado de Mato Grosso - Santos, Sinara Moreira de Freitas (2023)
Sport, a sociocultural phenomenon increasingly present in people's lives, allows the construction of different knowledge and values. As an activity, it involves children, young people and adults around the world, mobilizing different levels of sources of satisfaction. Satisfaction is an indicator of the sporting experience, being fundamental to understanding young people's participation in sport. In the school context, sport occupies an important space. From voluntary participation, practiced by students in the school environment, to external intercollegiate competitions, with teams formed to represent educational institutions in tournaments and sports competitions. Among school sporting activities in the State of Mato Grosso, the Youth School Games are one of the main sporting events, with representatives from various regions, in individual and collective modalities. Given this, the study addresses the following question: what effect do development assets have on young people's perception of satisfaction in sport? Thus, the study aims to analyze the perception of sources of satisfaction in sport and present the development assets in athletes participating in youth school games in the State of Mato Grosso. This is a cross-sectional, descriptive, quantitative study. The instruments used were two psychometric questionnaires and one sociodemographic questionnaire. To assess the perception of satisfaction in sport, the Sources of Satisfaction in Youth Sport (SEYSQ) questionnaire was used. To evaluate development assets, the Portuguese version of the Development Asset Profile Questionnaire (DAP) was used. 1258 young athletes participated in the study, students from public and private schools aged between 12 and 17 years old, participants in the state phase of the youth school games in 2019, in categories A and B. The analyzes were carried out using the software Rstudio version 4.2. two. Of the 1258 athletes, there was a slight predominance of males (54.9%) compared to females (45.1%). The average age of the participants was 14.7 years, with an age range that varied from 12 to 17 years. Many athletes were involved in intensive training programs, with 30.8% training more than 5 times a week and the majority of athletes were attending elementary school (54.2%) and high school (42.5%). Many athletes studied in the state public school system (64.9%), trained outside of school physical education class hours (87.4%) and competed at state level (41.9%). It was evident that a series of sociodemographic and sports involvement factors are related to students' satisfaction and perception of school and sport: the school environment plays a significant role in student satisfaction; the choice of sport also influences students' perception; there is a gender difference in students' perception of school and sport; there are perceived inequities in the school experience based on race; participation in school events, especially at the state level, is associated with a more positive perception of the school and support; Complementary sports activities play a role in student satisfaction. This study revealed a positive correlation between the perception of satisfaction and development assets in young athletes participating in youth school games in Mato Grosso. This indicates that the younger athletes experience competencies recognized by others, effort, affiliation with peers and self-referenced competencies, the greater their satisfaction in sport and their desire to continue participating.